Tourism storytelling research progress and trends: A systematic literature review on SDGs - Han Li; Shengke Zeng; Kaixin Tay (The global goals, 2024)
Introduction: As travelers seek safer, more meaningful experiences, storytelling has become vital in destination marketing. Aligned with the Sustainable Development Goals (SDGs), it promotes sustainable development, low-carbon practices, and eco-friendly tourism. Objective: The objective of this study is to investigate the current state, research hotspots, and emerging trends in storytelling within the tourism field, with the aim of providing a comprehensive overview of existing research, identifying key areas of focus, and highlighting potential directions for future studies. Method: The methodology adopted for this research comprises a bibliometric analysis of storytelling in the tourism field over the past 18 years, based on the Web of Science (WOS) database. The study design involved conducting co-authorship analysis, co-citation analysis, and keyword analysis using the visualization tool CiteSpace 6.1. Results: The results obtained revealed that both independent and collaborative research in this field are relatively limited, leading to a lower overall research impact. The lack of widely influential research outcomes has further affected the frequency of citations and the centrality of the literature within academic networks. Additionally, keyword analysis identified four key research areas in the current studies: the application of storytelling in destination marketing; pathways and methods for enhancing tourist experiences through storytelling; the use of storytelling in the promotion and preservation of cultural heritage; and the application of digital storytelling in tourism. Possible discrepancies and limitations of the study are also considered in this section.